The Value of Family History in Diagnosing Primary Immunodeficiency Disorders - Mohamed A. Hendaus; Ahmad Alhammadi; Mehdi M. Adeli; Fawzia Al-Yafei (Case Reports in Pediatrics)
Eliciting proper family medical history is critical in decreasing morbidity and mortality in patients with primary immunodeficiency disorders (PIDs). Communities with a common practice of consanguinity have a high rate of PIDs. We are presenting 2 cases where digging deeply into the family medical history resulted in the diagnosis of Omenn syndrome, a possibly fatal entity if not managed in a reasonable period.